Identifying the Causes and Extent of Insurance Deductions in a Hospital: An Interventional Approach to Cost Management - Roohangiz Taheri; Rohollah Kalhor; Bahman Ahadinezhad; Mohammad Zakaria Kiaei (Shahid Sadoughi University of Medical Sciences, 2020)
Background: A significant amount of revenues and deductions exist in the hospitals each year. This study aimed to determine the number of deductions applied and identify its causes. Furthermore, we aimed to provide management strategies to reduce these deductions in Shafa Takestan hospital. Methods: This applied and interventional study was conducted with a cross-sectional design. The data collection tool was a checklist from the previous studies. Data were analyzed using descriptive statistics such as mean, percentage, and standard deviation as well as analytical statistics of the Wilcoxon test. Results: Before the intervention, among 405 non-global inpatient cases, about 323 (80 %) contained subtractions. After the intervention, among 555 non-global hospital admissions, about 264 (47 %) included deductions. Most deductions were related to health services insurance (75.38 %). Concerning each hospital ward, most deductions were related to surgery ward (38 %). Before and after the intervention, service deductions were included in 5.59 % and 4.57 %, respectively. Conclusion: Therefore, medical personnel should pay more attention to documenting patientschr('39') records and minimizing documentation errors. Moreover, to reduce patient record deductions, the health care staff should be familiarized with proper documentation procedures by conducting training sessions.